Oxidative Stress and The Activities of Catalase , GST in Thalassemic Patients - Altai, W.F (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study concentrated on measuring the lipid peroxidation marker malon di aldehyde (MDA) in sera of thirty five patients with minor Thalassemia (Tm), thirty five with major Thalassemia (TM) and thirty five healthy control, their age ranged from (17-30) years. Erythrocytes enzymes (Glutathione -S - transferase (GST )and Catalase) were assayed . The results showed a significant elevation in (MDA) in sera of both patient groups compared to control. An increase in the activity of catalase and GST in erythrocytes of minor Thalassemic patients compared to control was found to be significant. Also, a high significant increase in the activity of GST for major Thalassemic patients compared to minor Thalassemic patients and control was found. On the other hand, the catalase activi ty for major Thalassemic patients was found in compatible with that of the control group.